Stavudine delivery in an extended release formulation: Will it provide the right in vivo pharmacokinetics — Some key observations - AJP, Editor (Asian Journal of Pharmaceutics (AJP), 2014)
Saravanakumar et al, (2010) have performed an extensive study to enable the delivery of stavudine in a once daily extended release formulation.[1] The in vitro evaluation has been performed with multiple formulation options to enable the selection of the right formulation system that renders once-a-day delivery of stavudine, ensuring that zero order release is maintained during the entire duration. As evidenced by the generated data, the recommended formulation (F9), appears to release approximately 4% of the drug load every hour leading to a complete release of the stavudine drug load by 24 hours.